2005
DOI: 10.3346/jkms.2005.20.3.438
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simvastatin on the Proliferation and Differentiation of Human Bone Marrow Stromal Cells

Abstract: Statins have been postulated to affect the bone metabolism. Recent experimental and epidemiologic studies have suggested that statins may also have bone protective effects. This study assessed the effects of simvastatin on the proliferation and differentiation of human bone marrow stromal cells (BMSCs) in an ex vivo culture. The bone marrow was obtained from healthy donors. Mononuclear cells were isolated and cultured to osteoblastic lineage. In the primary culture, 10-6 M simvastatin diminished the mean size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
79
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 43 publications
12
79
0
1
Order By: Relevance
“…0.5 g) would be diluted by 54 -153 ml of fluid after 24h. This would give rise to a dynamic concentration of simvastatin within the micromolar range, which could be expected to stimulate osteoblastic cells [27,[33][34][35]. The incorporation of simvastatin in brushite cement can therefore be expected to increase the effectiveness of the non-invasive treatment, this remaining to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…0.5 g) would be diluted by 54 -153 ml of fluid after 24h. This would give rise to a dynamic concentration of simvastatin within the micromolar range, which could be expected to stimulate osteoblastic cells [27,[33][34][35]. The incorporation of simvastatin in brushite cement can therefore be expected to increase the effectiveness of the non-invasive treatment, this remaining to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of the simvastatin solution was selected with three considerations in mind: 1) a simvastatin concentration between 0.01 and 1 ”M has been shown to promote osteoblastic differentiation in vitro [27,[33][34][35], 2) there is a dynamic exchange of interstitial fluids in vivo, flow rate in pig bones was estimated to be 7.5-21.3 ml/min/100g [36] and, 3) 1h-set cement released almost half of the dosage in 1 day (preliminary study using a simvastatin solution of 2 mM).…”
Section: Cement Preparationmentioning
confidence: 99%
“…The latter, in turn, are widely used to lower blood cholesterol level and can stimulate bone formation, as observed by the increasing activity of the alkaline phosphatase, osteocalcin expression levels and mineral deposits, suggesting an anabolic effect on bone tissue by increasing osteoblast differentiation 6 . Some studies suggest that simvastatin (SVT) enhances differentiation of osteoblasts in humans, measured by increased alkaline phosphatase activity and the expression of osteoblast-related genes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The materials available for bone regeneration are still expensive and unaffordable to many patients, and therefore, there is a tireless search by the scientific community for a biomaterial that is efficient and, at the same time, accessible to the majority of the population 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Previous in vivo studies showed that oral administration of a high dose of simvastatin (20 mg/kg/day) enhances trabecular bone volume in ovariectomized rats. 9, 16 Skoglund et al also reported that systemic administration of an extremely high dose of simvastatin (120 mg/kg/day) in mice increases bone healing.…”
mentioning
confidence: 99%